Synthesis and Biological Activity of 2-Arylidene-N-(quinolin-6-yl)hydrazine-1-carboxamides - Shengxian Zhao; Yin Cao; Zhenzhen Cui; Jiayun Zhang; Zhixiang Pan; Hongyu Hu (Journal of Chemistry)
A series of 2-arylidene-N-(quinolin-6-yl)hydrazine-1-carboxamides 5a–5o were synthesized and characterized. The synthesized compounds (5a–5o) were screened in vitro against three breast cancer cell lines: SKBR3, MDA-MB-231, and MCF-7 cancer cell lines by the MTT assay. According to MTT results, compounds 5k and 5l showed better antiproliferative activities over MCF-7 cell lines with IC50 values of 8.50 and 12.51 μM. Colony formation assay indicated 5k/5l treatment obviously inhibited the growth of MCF-7 cells and 5k/5l-induced cell cycle was arrested in the G2-M phase. Moreover, 5k/5l significantly increased the level of cleaved PARP and induced the apoptosis in MCF-7 cells. In addition, compared to Hela cells, MCF-7 cells were more sensitive to 5k/5l treatment.